Engagement in retirement: an evaluation of the effect of Active Mentoring on engagement of older adults with intellectual disability in mainstream community groups. (10th October 2012) - Chng, J. P. L.; Stancliffe, R. J.; Wilson, N. J.; Anderson, K.
Abstract Background As adults with intellectual disability age, retirement options need to be explored. One option is to attend a mainstream community group for retirees. Support within these groups could come from group members who are trained to act as mentors for the older adults with intellectual disability. This research evaluated a support training programme, Active Mentoring, which combines elements of Active Support and Co‐worker Training. Method Three older women with intellectual disability participated in a non‐concurrent multiple baseline design. Effect size analyses (Percentage of Non‐overlapping Data) were used to evaluate observational data. Results Active Mentoring was effective in increasing most types of engagement in activities, but there was no observed effect for social engagement. Mentor help also increased. Conclusion Active Mentoring was effective in eliciting support from mentors, and in increasing activity engagement of older adults with intellectual disability in mainstream community groups.